The Role of Big Data in Transforming HR Analytics and Talent Management Practices - Anwar, Umari Abdurrahim Abi; Senen, Syamsul Hadi; Rofaida, Rofi; Suwarsi, Sri (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2024)
Research Objective: This study aims to reveal the use of BD in the technological development of HRA applications for TM management. Approach: This study uses quantitative and qualitative methods. The quantitative method uses a differential test on the variable of BD usage. Furthermore, using the HRA system, the qualitative method uses descriptive analysis to manage TM. Research Findings: The study's results indicate differences in HRA management before and after using BD. Through BD, HR can analyze data from work performance, feedback, supervision, and talent profiles filled out by employees. This can help HRA identify hidden skills and abilities of employees and help develop them. Employees who can develop their talents well can be valuable company assets. Originality: This study is expected to empirically test the implications of using BD in HRA to manage TM in the company. Implications for practitioners: This study can encourage companies that have not used BD to consider using it to manage their HR. Research limitations: This study does not quantitatively test the effect of HRA on company performance but only uses the best practices of the companies that are respondents.